Egbert Jamieson, The Municipal Code of Chicago: Comprising the Laws of Illinois Relating to the City of Chicago, and the Ordinances of the City Council; Codified and Revised, Page 302, § 1271 - (:unkn) unknown (General Publisher, 1881)
Prohibited carrying or conveying any gunpowder or guncotton exceeding fifty pounds in quantity through any street, alley, highway, or road in the city, or within one miles of the limits thereof in any cart, carriage, wagon, dray, or wheelbarrow, or otherwise, unless secured in tight cases or kegs "well headed and hooped" and covered with a good and tight substantial leather bag sufficient to prevent the same from being spilled or scattered or placed into a perfect water tight box.
--
Keywords: GUN POWDER TRANSPORTATION